Vibronic Relaxation Pathways in Molecular Spin Qubit Na9[Ho(W5O18)2]·35H2O under Pressure - Janice L. Musfeldt; Zhenxian Liu; Diego López-Alcalá; Yan Duan; Alejandro Gaita-Ariño; José J. Baldoví; Eugenio Coronado (Magnetochemistry, 2023)
In order to explore how spectral sparsity and vibronic decoherence pathways can be controlled in a model qubit system with atomic clock transitions, we combined diamond anvil cell techniques with synchrotron-based far infrared spectroscopy and first-principles calculations to reveal the vibrational response of Na<semantics>9</semantics>[Ho(W<semantics>5</semantics>O<semantics>18</semantics>)<semantics>2</semantics>]·35H<semantics>2</semantics>O under compression. Because the hole in the phonon density of states acts to reduce the overlap between the phonons and f manifold excitations in this system, we postulated that pressure might move the HoO<semantics>4</semantics> rocking, bending, and asymmetric stretching modes that couple with the <semantics>MJ</semantics> = ±5, ±2, and ±7 levels out of resonance, reducing their interactions and minimizing decoherence processes, while a potentially beneficial strategy for some molecular qubits, pressure slightly hardens the phonons in Na<semantics>9</semantics>[Ho(W<semantics>5</semantics>O<semantics>18</semantics>)<semantics>2</semantics>]·35H<semantics>2</semantics>O and systematically fills in the transparency window in the phonon response. The net result is that the vibrational spectrum becomes less sparse and the overlap with the various <semantics>MJ</semantics> levels of the Ho<semantics>3+</semantics> ion actually increases. These findings suggest that negative pressure, achieved using chemical means or elongational strain, could further open the transparency window in this rare earth-containing spin qubit system, thus paving the way for the use of device surfaces and interface elongational/compressive strains to better manage decoherence pathways.